IS COGNITIVE DECLINE BEFORE DEATH IN THE OLDEST OLD A UNIVERSAL PHENOMENON?. (11th November 2018) - Robitaille, A; Cadar, D; Koval, A; Jagger, C; Johansson, B; Hofer, S; Piccinin, A; Muniz-Terrera, G
Abstract: We investigated the heterogeneity in end of life cognitive decline in two European longitudinal studies of the oldest old: the OCTO-Twin and the Newcastle 85+ Study. Using a coordinated analytical approach, we identified unobserved groups of individuals with similar trajectories of cognitive decline at the end of life by fitting Tobit Growth Mixture Models to Mini-Mental State Examination scores. In both studies, the current analyses consistently identified two groups of individuals whose cognitive decline at the end of life were distinct: one group did not exhibit an ostensible rate of decline, another group experienced steep decline in measures of global cognition within each study. In OCTO-Twin, accelerated decline was found in only one group. Our results showed heterogeneity in cognitive decline at the end of life in the oldest old across two different European countries and suggest that terminal decline is not necessarily a normative process.